Los emprendimientos como alternativa de desarrollo local en el cantón Guamote, provincia de Chimborazo. - Wilman Gustavo Carrillo Pulgar (2022)
ABSTRACT: Nowadays, entrepreneurship has become a fundamental pillar for the economic and local development of a country, since it potentiates the internal or endogenous business fabric of a territory or locality. At the same time, this activity drives the improvement of the population's quality of life. Commercial activity has a great impact on the socioeconomic life of the Guamote canton, gaining importance since the 1990s with the support of public and private institutions and NGOs. Most of the production is destined for self-consumption and the little that is produced is commercialized in the same communities and Thursday fairs with the objective of promoting local development in the canton. It is for these reasons that the present study had as its objective: "To analyze the impact of the enterprises in the local development of the Guamote canton, province of Chimborazo", the methodology of descriptive type research is applied with a quantitative approach to process the statistical analysis and the qualitative approach with the modality of bibliographic-documentary and field research where the basic instrument of the research was precisely a survey directed to the managers owners of the enterprises; social and religious, service, industrial, productive, financial and associative or community enterprises, with the purpose of gathering relevant information, to later enter the results in the SPSS program for the respective verification of Hypotheses. The conclusion is that entrepreneurship continuously contributes to local development by generating sources of work that allow improving the population's standard of living based on community collaboration and solidarity economy; above all, entrepreneurship has made the Guamote canton to develop economically and financially.